Endopeptidase inhibition attenuates the contraction induced by big endothelin‐1 of isolated human penile erectile tissue. (25th March 2018) - Shahin, P.; Rahardjo, H. E.; Bannowsky, A.; Tsikas, D.; Sohn, M.; Kuczyk, M. A.; Ückert, S.
Summary: Peptides, such as C‐type natriuretic peptide (CNP), vasoactive intestinal polypeptide (VIP) and endothelin 1 (ET‐1), are involved in the control of penile erectile tissue (corpus cavernosum = CC). Inhibiting the degradation of CNP and VIP or conversion of Big ET‐1 into ET‐1 by endopeptidase enzymes should result in an enhancement of CC smooth muscle relaxation. Using the tissue bath technique, responses of isolated CC, challenged by noradrenaline (NA, 1 μm ), to increasing concentrations of the endopeptidase inhibitor KC 12615 (1 nm – 10 μm ), CNP and VIP (0.1 nm – 1 μm ), were investigated. Effects of CNP, VIP and Big ET‐1 (0.1 nm – 100 nm ) on the tissue tension were also evaluated following pre‐exposure to 10 μm of KC 12615. Big ET‐1 induced contraction of the CC amounting to a force generation of 1, 200 mg. The contraction was attenuated in the presence of KC 12615 by 35% and 50%, respectively. The tension induced by NA was reversed by VIP and CNP to 38.7% ± 15.8% and 61% ± 13%, respectively, of the initial force. The findings might be of significance with regard to future pharmacological treatment options for male ED, where an endothelial dysfunction exists.